2014
DOI: 10.3389/fnagi.2014.00289
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive stimulation of prefrontal cortex strengthens existing episodic memories and reduces forgetting in the elderly

Abstract: Memory consolidation is a dynamic process. Reactivation of consolidated memories by a reminder triggers reconsolidation, a time-limited period during which existing memories can be modified (i.e., weakened or strengthened). Episodic memory refers to our ability to recall specific past events about what happened, including where and when. Difficulties in this form of long-term memory commonly occur in healthy aging. Because episodic memory is critical for daily life functioning, the development of effective int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
149
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(166 citation statements)
references
References 88 publications
13
149
3
1
Order By: Relevance
“…For example, stimulation immediately after, but not during, training of a finger-tapping task enhanced subsequent performance 30 min later, presumably by facilitating early consolidation of procedural memory (Tecchio et al 2010). Similarly, reactivation of a previously learned word list hours or a day later led to better retention if stimulation was administered directly during this reactivation/reconsolidation period (Javadi and Cheng 2013;Sandrini et al 2014). Furthermore, stimulation during sleep seems especially fruitful for declarative memory enhancement if timed during the appropriate consolidation period during slow-wave sleep (Barham et al 2016).…”
Section: Timing Of Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, stimulation immediately after, but not during, training of a finger-tapping task enhanced subsequent performance 30 min later, presumably by facilitating early consolidation of procedural memory (Tecchio et al 2010). Similarly, reactivation of a previously learned word list hours or a day later led to better retention if stimulation was administered directly during this reactivation/reconsolidation period (Javadi and Cheng 2013;Sandrini et al 2014). Furthermore, stimulation during sleep seems especially fruitful for declarative memory enhancement if timed during the appropriate consolidation period during slow-wave sleep (Barham et al 2016).…”
Section: Timing Of Stimulationmentioning
confidence: 99%
“…Therefore, it is conceivable that tDCS, with its putative effects on cortical excitability (which may operate via glial-neuron interactions rather than neural stimulation directly), could enhance neural replay and therefore enhance consolidation. Though a direct demonstration is lacking, several studies have applied tDCS during waking rest at time periods when replay is thought to occur (Javadi and Cheng 2013;Sandrini et al 2014;Tecchio et al 2010) and subsequently demonstrated greater consolidation. Similarly, the application of slow-oscillating tDCS during slow-wave sleep has been shown to enhance declarative memory (reviewed in Barham et al 2016).…”
Section: Neurobiology Of Consolidation and Tdcsmentioning
confidence: 99%
“…The 25 qualified studies were submitted to our meta-analysis. One author (NK) independently coded the 25 studies and extracted data (Berryhill and Jones, 2012;Boggio et al, 2010;Fertonani et al, 2014;Floel et al, 2012;Goodwill et al, 2015;Goodwill et al, 2013;Hardwick and Celnik, 2014;Harty et al, 2014;Heise et al, 2014;Hoff et al, 2015;Holland et al, 2011;Hummel et al, 2010;Jones et al, 2015;Lindenberg et al, 2013;Manenti et al, 2013;Meinzer et al, 2013;Meinzer et al, 2014;Panouilleres et al, 2015;11 Parikh and Cole, 2014;Park et al, 2014;Ross et al, 2011;Sandrini et al, 2014;Seo et al, 2011;Zhou et al, 2015;Zimerman et al, 2013). Two authors (JS & JC) confirmed data extractions, and all authors were involved in interpreting the meta-analytic results.…”
Section: Study Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…In addition, increased excitability of the left frontal lobes during retention period (between encoding and recall) was associated with reduced forgetting in healthy older adults (Sandrini et al, 2014). Thirty-six healthy older adults were divided into anodal left DLPFC tDCS and sham stimulation groups and participated over 4 sessions.…”
Section: Left Prefrontal Cortex Stimulationmentioning
confidence: 99%